Bone mineral density and bone mineral content estimation using low-cost x-ray detector - Chuaychunu, N.; Pititheerapab, Y.; Chanwimalueang, T.; Lertprasert, P.; Pintavirooj, C. (My University, 2007)
This paper presented a design of a low-cost x-ray-detector using CMOS camera with an application on bone mineral content estimation. The main components consist of CMOS camera, optical lens, and image intensifier screen. CMOS camera offers various advantages including miniature-sized, low power consumption and cost effective. To apply the CMOS camera as x-ray detector, x-ray-to-visible light convector is required. Our key component of x-ray-to-visible light converter is intensifier screen. The application of x-ray detector for bone mineral density (BMD) and bone mineral content (BMC) is also given in this paper. The concept of dual energy x-ray is adopted to estimate the BMD on the finger bone. To compute BMC from BMD, the area of the bone is required. The concept of aative contour is applied to estimate the finger-bone area. ©2007 IEEE.
Keywords: BMC; BMD; Dual energy x-ray